A INFLUÊNCIA DA EDUCAÇÃO FÍSICA COMO DISCIPLINA ESCOLAR NA FORMAÇÃO DE CIDADÃOS - Trindade, Tiego Dias (2024)
This research analyzes the influence of Physical Education as a school subject in the formation of citizens. The genesis of Physical Education as a school discipline in Brazil included elements of disciplinary training, the ability to collaborate in sports, and involvement in practices aimed at playfulness and health. In this sense, Physical Education was not a curricular component aimed at preparing for entrance exams to higher education, but rather aimed at broader student development. With the implementation of Physical Education content in examination matrices such as the National High School Exam (ENEM), the configuration changed. Therefore, this research aimed to analyze the preparation of lesson plans by Physical Education teachers, especially those teaching the third year, at a Military School in Southern Brazil. Documents such as the National Curriculum Parameters (PCNs) for Physical Education and the Common National Curriculum Base (BNCC) were analyzed to understand the objective of the curricular component, whether it should be focused on selection exams and/or citizen formation. It was concluded that although the focus on exams is relevant, by moving from the court to the classroom, Physical Education reinforces its importance in citizen formation.